Management of Stage 1 Hypertension in Adults With a Low 10-Year Risk for Cardiovascular Disease: Filling a Guidance Gap. Issue 6 (June 2021) - Jones, Daniel W.; Whelton, Paul K.; Allen, Norrina; Clark, Donald; Gidding, Samuel S.; Muntner, Paul; Nesbitt, Shawna; Mitchell, Nia S.; Townsend, Raymond; Falkner, Bonita
Abstract : High blood pressure (BP) is the leading cause of worldwide cardiovascular disease morbidity and mortality. Patients and clinicians dealing with hypertension have benefited from the evidence of event-based randomized controlled clinical trials. One result from those trials has been the development of evidence-based guidelines. The commitment to using evidence from these event-based randomized trials has been a cornerstone in the development of guideline treatment recommendations. However, in some situations, evidence from event-based trials is not available to guideline writers or clinicians for assistance in treatment decision making. Such is the case for the management of many patients with stage 1 hypertension. The purpose of this scientific statement is to provide information complementary to the 2017 Hypertension Clinical Practice Guidelines for the patient with untreated stage 1 hypertension (systolic BP/diastolic BP, 130–139/80–89 mm Hg) with a 10-year risk for atherosclerotic cardiovascular disease <10% who fails to meet the systolic BP/diastolic goal (<130/80 mm Hg) after 6 months of guideline-recommended lifestyle therapy. This statement provides evidence from sources other than event-based randomized controlled clinical trials and offers therapy options for consideration by clinicians.